Novel polymer-based heat conduction material and preparation method thereof

Through the crosslinking technology of homemade composite three-dimensional thermal conductivity fillers and silicone oil, the unpredictability of the thermal conductivity path of traditional thermal conductivity materials is solved, efficient heat conduction is achieved, and the thermal conductivity of polymer-based thermal conductivity is significantly improved.

CN119505540APending Publication Date: 2025-02-25KUSN ZHONGDI MATERIALS TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458751.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When traditional filler thermal conductivity of composite materials improves the thermal conductivity of composite materials, the thermal conductivity paths constructed by high thermal fillers in polymer materials are unpredictable, resulting in the inability to significantly improve the thermal conductivity of composite materials.

Method used

The homemade composite three-dimensional thermal conductivity filler is made mainly from dextran, graphene, nanosilica, silane coupling agent, sodium chloride and polystyrene. It is crosslinked with silicone oil and metal-based catalyst to form a stable organic three-dimensional framework that complements the composite three-dimensional thermal conductivity framework to improve thermal conductivity.

Benefits of technology

By forming a uniform and stable composite three-dimensional thermal conductivity framework, the dispersion of the filler is optimized, the contact thermal resistance is reduced, and the thermal conductivity of polymer-based thermal conductivity is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091245960000071
    Figure BDA0005091245960000071
Patent Text Reader

Abstract

The invention discloses a novel polymer-based heat conduction material and a preparation method thereof, and relates to the technical field of polymer-based heat conduction materials. The preparation method comprises the following steps: pretreating graphene and nano silicon dioxide by using a silane coupling agent, modifying the graphene and nano silicon dioxide by using dextran, and constructing a graphene-dextran-silicon dioxide composite three-dimensional heat-conducting filler by using sodium chloride as a sacrificial template and polystyrene as an adhesive to form a novel composite filler; and crosslinking the composite three-dimensional heat-conducting filler with silicone oil to obtain the novel polymer-based heat-conducting material. The prepared novel polymer-based heat conduction material has two types of three-dimensional heat conduction structures, heat transfer paths are increased, the heat conduction coefficient of the material is improved, the whole system has a better heat conduction effect, active hydroxyl in glucan and silicone oil form firmer crosslinking, the stability of the silicone oil is enhanced, and the heat conduction performance of the material is improved. The novel polymer-based heat-conducting material with high stability and strong heat conductivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive materials, and in particular to a novel polymer-based thermal conductive material. Background Art

[0002] With the rise of industries such as 5G communications, energy, and smart manufacturing, electronic equipment is rapidly developing towards high integration, multi-functions, and miniaturization. Correspondingly, the volume of electronic components and logic circuits has shrunk by tens of millions of times, while the operating frequency has increased dramatically. At this time, the heat generated by electronic equipment accumulates and increases rapidly, and the working environment temperature also changes rapidly towards high temperature. In order to ensure that components can still operate normally and reliably, timely heat dissipation has become a key technology that restricts service life. Therefore, with the miniaturization and high performance of electronic components, higher requirements are placed on the thermal conductivity of materials.

[0003] Traditional filled thermally conductive polymer materials usually use a single high thermal conductivity material as a filler. Usually, to improve the thermal conductivity of composite materials, it is necessary to form a continuous thermal conductivity path in the substrate. Therefore, in order to increase the thermal conductivity of composite materials, it is usually necessary to add a large amount of fillers to the substrate during the preparation of the composite materials to construct a continuous filler structure to form a thermal conductivity path. However, the thermal conductivity path constructed by the directly filled high thermal conductivity filler in the polymer material is unpredictable, which ultimately leads to the inability to significantly improve the thermal conductivity of the composite material. Summary of the invention

[0004] The purpose of the present invention is to provide a novel polymer-based thermal conductive material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a new polymer-based thermal conductive material, wherein the new polymer-based thermal conductive material comprises a self-made composite three-dimensional thermal conductive filler, silicone oil, and a metal-based catalyst.

[0006] Furthermore, the self-made composite three-dimensional thermal conductive filler is mainly prepared from dextran, graphene, nano-silicon dioxide, silane coupling agent, sodium chloride and polystyrene.

[0007] Furthermore, the silicone oil is one or more of vinyl silicone oil and hydrogen-containing silicone oil.

[0008] Furthermore, the metal-based catalyst is one or more of a platinum-based catalyst, a copper-based catalyst, a zinc-based catalyst, and a platinum catalyst.

[0009] Furthermore, the silane coupling agent includes one or more of aminopropyltrimethoxysilane, diaminodiphenylsiloxane, and diaminodiethylsiloxane.

[0010] A method for preparing a novel polymer-based thermal conductive material comprises the following preparation steps:

[0011] (1) adding 10 to 20 parts of graphene and 10 to 20 parts of nano-silicon dioxide with a particle size of 30 to 80 nm to 40 to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically dispersing at a frequency of 50 to 200 kHz for 20 to 50 minutes to obtain solution A; adding 10 to 40 parts of silane coupling agent to 40 to 70 parts of water, and stirring at a rate of 100 to 400 r / min at 40 to 70° C. for 20 to 50 minutes to obtain solution B; adding solution A to solution B at 40 to 80° C. B, stirring at a rate of 300-600 r / min for 4-8 hours to obtain solution C; at 70-100°C, dissolving 40-60 parts of dextran in 50-100 parts of water, stirring at a rate of 200-600 r / min for 20-50 minutes to obtain solution D; under heating and stirring, adding solution C to solution D, stirring for a certain period of time, cooling the obtained solution to room temperature, filtering out the solid, and drying at 50-80°C for 2-4 hours to obtain a modified composite thermal conductive filler;

[0012] (2) Weigh 1 to 4 parts of polystyrene, add it to 5 to 20 parts of chloroform, and ultrasonically disperse it at a frequency of 50 to 200 kHz for 40 to 80 minutes to obtain solution E; weigh 10 to 20 parts of sodium chloride and 1 to 5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 100 to 200 r / min for 20 to 80 minutes to obtain solution F, place solution F in a fume hood for 5 to 8 hours to remove chloroform, and then place it in an oven and dry it at 50 to 80° C. for 1 to 4 hours, add the obtained substance to 150 to 300 parts of deionized water, stir it at a rate of 100 to 200 r / min for 10 to 20 minutes, stand it for 3 to 6 hours, remove the upper solution, place it in an oven, and dry it at 50 to 80° C. for 2 to 4 hours to obtain a solid filler, and repeat the process of removing sodium chloride 3 to 5 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0013] (3) Adding a self-made composite three-dimensional thermal conductive filler and a metal-based catalyst to the silicone oil while heating and stirring, and continuously stirring for a certain period of time to obtain a new polymer-based thermal conductive material.

[0014] Furthermore, the heating and stirring in step (1) are as follows: the reaction temperature is 70-100° C., the reaction time is 2-6 hours, and the stirring rate is 300-600 r / min.

[0015] Furthermore, in the step (3), the silicone oil stirring reaction temperature is 50-100° C., the reaction time is 3-6 hours, and the stirring rate is 400-600 r / min.

[0016] Furthermore, in the step (3), the mass ratio of silicone oil, self-made composite three-dimensional thermal conductive filler, and metal-based catalyst is 50-100:20-40:1-5.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] The novel polymer-based thermal conductive material prepared by the present invention is firstly pre-treated with a silane coupling agent for graphene and nano-silica, then modified with dextran, and then constructed with sodium chloride as a sacrificial template and polystyrene as an adhesive to form a graphene-dextran-silica composite three-dimensional thermal conductive filler to form a novel composite filler, and then the composite three-dimensional thermal conductive filler is cross-linked with silicone oil to obtain a novel polymer-based thermal conductive material.

[0019] First, dextran is used to composite-modify graphene and nano-silica, so that there are more organic functional groups on the surface of the modified graphene and nano-silica, which optimizes the dispersibility of the composite filler, forms a more uniform and stable composite three-dimensional thermal conductive skeleton, and achieves a high heat dissipation effect. The use of graphene and nano-silica fillers can effectively reduce the contact thermal resistance caused by single-component fillers, enhance the thermal conductivity of the system, and ultimately effectively improve the thermal conductivity of the entire thermal conductive material.

[0020] Secondly, the use of dextran adds a large number of active hydroxyl groups to the filler. When cross-linked with silicone oil, it can form chemical bonds to form an organic three-dimensional skeleton with silicone oil to obtain a gel with strong stability. The organic three-dimensional network structure in the gel and the composite three-dimensional thermal conductive skeleton formed by the modified filler are interspersed and complement each other to obtain two types of composite three-dimensional thermal conductive skeletons, which provide a large number of paths for heat conduction and further improve the thermal conductivity of polymer-based thermal conductive materials. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the novel polymer-based thermal conductive materials prepared in the following examples are as follows:

[0023] Thermal conductivity test: The thermal conductivity of the novel polymer-based thermal conductive materials prepared in each embodiment and comparative example was tested according to ASTM D 5470-2006 standard.

[0024] Example 1

[0025] (1) Add 10 parts of graphene and 20 parts of nano-silica with a particle size of 50 nm to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically disperse at a frequency of 150 kHz for 30 minutes to obtain solution A; add 10 parts of diaminodiphenylsiloxane to 70 parts of water, and stir at a rate of 200 r / min for 30 minutes at 50°C to obtain solution B; add solution A to solution B at 50°C, and stir at a rate of 400 r / min for 5 hours to obtain solution C; dissolve 40 parts of dextran in 100 parts of water at 90°C, and stir at a rate of 400 r / min for 50 minutes to obtain solution D; add solution C to solution D under heating and stirring at 90°C, and continue stirring at a rate of 400 r / min for 3 hours, cool the obtained solution to room temperature, filter out the solid, and dry it at 70°C for 2 hours to obtain a modified composite thermal conductive filler;

[0026] (2) Weigh 1 part of polystyrene, add it to 15 parts of chloroform, and ultrasonically disperse it at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 10 parts of sodium chloride and 1 part of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper layer of solution is removed, and the solution is placed in an oven and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0027] (3) Add 20 parts of a self-made composite three-dimensional thermal conductive filler and 1 part of a platinum-based catalyst to 50 parts of vinyl-terminated polydimethylsiloxane at 70°C at a rate of 400 r / min while stirring, and continue stirring for 5 hours to obtain a new polymer-based thermal conductive material.

[0028] Example 2

[0029] (1) 15 parts of graphene and 15 parts of nano-silica with a particle size of 50 nm were added to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically dispersed at a frequency of 150 kHz for 30 minutes to obtain solution A; 20 parts of diaminodiphenylsiloxane were added to 70 parts of water, and stirred at a rate of 200 r / min for 30 minutes at 50° C. to obtain solution B; at 50° C., solution A was added to solution B, and stirred at a rate of 400 r / min for 5 hours to obtain solution C; at 90° C., 50 parts of dextran were dissolved in 100 parts of water, and stirred at a rate of 400 r / min for 50 minutes to obtain solution D; under heating and stirring at 90° C., solution C was added to solution D, and stirred at a rate of 400 r / min for 3 hours, the obtained solution was cooled to room temperature, the solid was filtered out, and dried at 70° C. for 2 hours to obtain a modified composite thermal conductive filler;

[0030] (2) Weigh 2 parts of polystyrene, add them to 15 parts of chloroform, and ultrasonically disperse them at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 15 parts of sodium chloride and 3 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper layer of solution is removed, and the solution is placed in an oven and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0031] (3) Add 30 parts of a self-made composite three-dimensional thermal conductive filler and 3 parts of a platinum-based catalyst to 80 parts of vinyl-terminated polydimethylsiloxane at 70°C at a rate of 400 r / min while stirring, and continue stirring for 5 hours to obtain a new polymer-based thermal conductive material.

[0032] Example 3

[0033] (1) Add 20 parts of graphene and 10 parts of nano-silica with a particle size of 50 nm to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically disperse at a frequency of 150 kHz for 30 minutes to obtain solution A; add 40 parts of diaminodiphenylsiloxane to 70 parts of water, and stir at a rate of 200 r / min for 30 minutes at 50°C to obtain solution B; add solution A to solution B at 50°C, and stir at a rate of 400 r / min for 5 hours to obtain solution C; dissolve 60 parts of dextran in 100 parts of water at 90°C, and stir at a rate of 400 r / min for 50 minutes to obtain solution D; add solution C to solution D under heating and stirring at 90°C, and continue stirring at a rate of 400 r / min for 3 hours, cool the obtained solution to room temperature, filter out the solid, and dry it at 70°C for 2 hours to obtain a modified composite thermal conductive filler;

[0034] (2) Weigh 4 parts of polystyrene, add them to 15 parts of chloroform, and ultrasonically disperse them at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 20 parts of sodium chloride and 5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper solution is removed, placed in an oven, and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0035] (3) To 100 parts of vinyl-terminated polydimethylsiloxane, 40 parts of a self-made composite three-dimensional thermally conductive filler and 5 parts of a platinum-based catalyst were added at 70°C at a rate of 400 r / min while stirring, and the mixture was stirred for 5 hours to obtain a new polymer-based thermally conductive material.

[0036] Comparative Example 1

[0037] (1) Add 20 parts of graphene to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically disperse at a frequency of 150 kHz for 30 minutes to obtain solution A; add 20 parts of silane coupling agent to 70 parts of water, and stir at a rate of 200 r / min for 30 minutes at 50°C to obtain solution B; add solution A to solution B at 50°C, and stir at a rate of 400 r / min for 5 hours to obtain solution C; dissolve 50 parts of dextran in 100 parts of water at 90°C, and stir at a rate of 400 r / min for 50 minutes to obtain solution D; add solution C to solution D under heating and stirring at 90°C, and continue stirring at a rate of 400 r / min for 3 hours, cool the obtained solution to room temperature, filter out the solid, and dry it at 70°C for 2 hours to obtain a modified composite thermal conductive filler;

[0038] (2) Weigh 4 parts of polystyrene, add them to 15 parts of chloroform, and ultrasonically disperse them at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 20 parts of sodium chloride and 5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper solution is removed, placed in an oven, and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0039] (3) Add 40 parts of material to 100 parts of vinyl-terminated polydimethylsiloxane at 70°C at a rate of 400 r / min while stirring.

[0040] Comparative Example 2

[0041] (1) Add 10 parts of nano-silica with a particle size of 50 nm to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically disperse at a frequency of 150 kHz for 30 minutes to obtain solution A; add 20 parts of diaminodiphenylsiloxane to 70 parts of water, and stir at a rate of 200 r / min for 30 minutes at 50° C. to obtain solution B; add solution A to solution B at 50° C. and stir at a rate of 400 r / min for 5 hours to obtain solution C; dissolve 50 parts of dextran in 100 parts of water at 90° C. and stir at a rate of 400 r / min for 50 minutes to obtain solution D; add solution C to solution D under heating and stirring at 90° C. and continue stirring at a rate of 400 r / min for 3 hours, cool the obtained solution to room temperature, filter out the solid, and dry it at 70° C. for 2 hours to obtain a modified composite thermal conductive filler;

[0042] (2) Weigh 4 parts of polystyrene, add them to 15 parts of chloroform, and ultrasonically disperse them at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 20 parts of sodium chloride and 5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper solution is removed, placed in an oven, and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0043] (3) To 100 parts of vinyl-terminated polydimethylsiloxane, 40 parts of a self-made composite three-dimensional thermally conductive filler and 5 parts of a platinum-based catalyst were added at 70°C at a rate of 400 r / min while stirring, and the mixture was stirred for 5 hours to obtain a new polymer-based thermally conductive material.

[0044] Comparative Example 3

[0045] (1) adding 20 parts of graphene and 10 parts of nano-silica with a particle size of 50 nm to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically dispersing at a frequency of 150 kHz for 30 minutes to obtain solution A; adding 20 parts of diaminodiphenylsiloxane to 70 parts of water, and stirring at a rate of 200 r / min for 30 minutes at 50° C. to obtain solution B; adding solution A to solution B at 50° C., and stirring at a rate of 400 r / min for 5 hours to obtain solution C; cooling the obtained solution to room temperature, filtering out the solid, and drying at 70° C. for 2 hours to obtain a modified composite thermal conductive filler;

[0046] (2) Weigh 4 parts of polystyrene, add them to 15 parts of chloroform, and ultrasonically disperse them at a frequency of 200 kHz for 50 minutes to obtain solution E; weigh 20 parts of sodium chloride and 5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 200 r / min for 50 minutes to obtain solution F, place solution F in a fume hood for 7 hours, remove chloroform, and then put it in an oven and dry it at 70°C for 3 hours. The obtained substance is added to 200 parts of deionized water, stirred at a rate of 200 r / min for 20 minutes, and after standing for 5 hours, the upper solution is removed, placed in an oven, and dried at 70°C for 4 hours to obtain a solid filler. The process of removing sodium chloride is repeated 4 times to finally obtain a self-made composite three-dimensional thermal conductive filler;

[0047] (3) To 100 parts of vinyl-terminated polydimethylsiloxane, 40 parts of a self-made composite three-dimensional thermally conductive filler and 5 parts of a platinum-based catalyst were added at 70°C at a rate of 400 r / min while stirring, and the mixture was stirred for 5 hours to obtain a new polymer-based thermally conductive material.

[0048] Comparative Example 4

[0049] (1) Dissolve 50 parts of dextran in 100 parts of water at 90°C and stir at a rate of 400 r / min for 50 min to obtain solution D;

[0050] (2) Add 40 parts of solution D and 5 parts of a platinum-based catalyst to 100 parts of vinyl-terminated polydimethylsiloxane at 70° C. and stirring at a rate of 400 r / min. After continuous stirring for 5 hours, a new polymer-based thermal conductive material is obtained.

[0051] Comparative Example 5

[0052] (1) Add 20 parts of graphene and 10 parts of nano-silica with a particle size of 50 nm to 70 parts of 95% ethanol aqueous solution by volume, and ultrasonically disperse at a frequency of 150 kHz for 30 minutes to obtain solution A; add 40 parts of diaminodiphenylsiloxane to 70 parts of water, and stir at a rate of 200 r / min for 30 minutes at 50°C to obtain solution B; add solution A to solution B at 50°C, and stir at a rate of 400 r / min for 5 hours to obtain solution C; dissolve 60 parts of dextran in 100 parts of water at 90°C, and stir at a rate of 400 r / min for 50 minutes to obtain solution D; add solution C to solution D under heating and stirring at 90°C, and continue stirring at a rate of 400 r / min for 3 hours, cool the obtained solution to room temperature, filter out the solid, and dry it at 70°C for 2 hours to obtain a modified composite thermal conductive filler;

[0053] (2) To 100 parts of vinyl-terminated polydimethylsiloxane, 40 parts of a self-made composite three-dimensional thermally conductive filler and 5 parts of a platinum-based catalyst were added at 70°C at a rate of 400 r / min while stirring, and the mixture was stirred for 5 hours to obtain a new polymer-based thermally conductive material.

[0054] Effect example

[0055] Table 1 below shows the performance analysis results of the novel polymer-based thermally conductive materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0056] Table 1 Thermal conductivity of the novel polymer-based thermal conductive materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5

[0057]

[0058] From the results in Table 1 above, compared with Example 3, Comparative Example 1 and Comparative Example 2, we found that when graphene and nano-silicon dioxide are used as thermally conductive fillers, the use of two thermally conductive fillers is better than using a single thermally conductive filler. When a single thermally conductive filler is added, the thermal conductivity is relatively simple, and it is easy to form a contact thermal resistance while forming a three-dimensional thermally conductive skeleton. The use of a two-component thermally conductive filler can effectively reduce the formation of contact thermal resistance, so that the thermal conductivity efficiency is better improved. Comparing the experimental results of Example 3 and Comparative Example 3, we found that the addition of dextran can also effectively improve the thermal conductivity of the polymer base. This is mainly due to the effective cross-linking of the active hydroxyl groups in the dextran and the amino groups in the silicone oil. The formation of chemical bonds gives the polymer a stable organic three-dimensional skeleton, and this three-dimensional skeleton also constitutes one of the paths of heat conduction. Comparing Example 3 and Comparative Example 5, the salt template method is used to form a three-dimensional thermally conductive skeleton for the filler, which can effectively improve the thermal conductivity of the material. When the salt template method is not used, the filler is only uniformly dispersed in the entire polymer system, and it is not easy to form a three-dimensional thermally conductive skeleton. Although the thermal conductivity is increased, the improvement effect is not ideal. The organic three-dimensional network formed by cross-linking dextran and silicone oil and the formed composite three-dimensional skeleton complement each other, so that the thermal conductivity efficiency can be further improved.

[0059] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A novel polymer-based thermal conductive material, characterized in that: The novel polymer-based thermal conductive material comprises a self-made composite three-dimensional thermal conductive filler, silicone oil, and a metal-based catalyst.

2. A novel polymer-based thermal conductive material according to claim 1, characterized in that: The self-made composite three-dimensional thermal conductive filler is mainly prepared from dextran, graphene, nano silicon dioxide, a silane coupling agent, sodium chloride and polystyrene.

3. A novel polymer-based thermal conductive material according to claim 1, characterized in that: The silicone oil is one or more of vinyl silicone oil and hydrogen-containing silicone oil.

4. A novel polymer-based thermal conductive material according to claim 1, characterized in that: The metal-based catalyst is one or more of a platinum-based catalyst, a copper-based catalyst, a zinc-based catalyst, and a platinum catalyst.

5. A novel polymer-based thermal conductive material according to claim 2, characterized in that: The silane coupling agent includes one or more of aminopropyltrimethoxysilane, diaminodiphenylsiloxane and diaminodiethylsiloxane.

6. A method for preparing a novel polymer-based thermal conductive material, characterized in that: The method comprises the following preparation steps: (1) Add 10-20 parts of graphene and 10-20 parts of nano-silica with a particle size of 30-80 nm to 40-70 parts of 95% ethanol aqueous solution, and ultrasonically disperse at a frequency of 50-200 kHz for 20-50 min to obtain solution A. Add 10-40 parts of silane coupling agent to 40-70 parts of water, and stir at a rate of 100-400 r / min at 40-70°C for 20-50 min to obtain solution B. At 40-80°C, add solution A to solution B and stir at a rate of 300-600 r / min for 4-8 hours to obtain solution C; At 70-100°C, dissolve 40-60 parts of dextran in 50-100 parts of water, and stir at a rate of 200-600 r / min for 20-50 min to obtain solution D; Under heating and stirring conditions, solution C is added to solution D, and stirring is continued for a certain period of time. The obtained solution is cooled to room temperature, solids are collected by filtration, and dried at 50-80° C. for 2-4 hours to obtain a modified composite thermally conductive filler. (2) Weigh 1-4 parts of polystyrene, add it to 5-20 parts of chloroform, and ultrasonically disperse it at a frequency of 50-200kHz for 40-80min to obtain solution E; weigh 10-20 parts of sodium chloride and 1-5 parts of modified composite thermal conductive filler, add them to solution E, stir at a rate of 100-200r / min for 20-80min to obtain solution F, place solution F in a fume hood for 5-8h to remove chloroform, then place it in an oven and dry it at 50-80℃ for 1-4h, add the obtained substance to 150-300 parts of deionized water, stir it at a rate of 100-200r / min for 10-20min, let it stand for 3-6h, remove the upper layer of solution, place it in an oven, and dry it at 50-80℃ for 2-4h to obtain a solid filler, repeat the process of removing sodium chloride 3-5 times, and finally obtain a self-made composite three-dimensional thermal conductive filler; (3) Adding a self-made composite three-dimensional thermal conductive filler and a metal-based catalyst into the silicone oil while heating and stirring, and continuing stirring for a certain period of time to obtain a new polymer-based thermal conductive material.

7. The method for preparing a novel polymer-based thermal conductive material according to claim 6, characterized in that: The heating and stirring in step (1) are as follows: the reaction temperature is 70-100° C., the reaction time is 2-6 h, and the stirring rate is 300-600 r / min.

8. The method for preparing a novel polymer-based thermal conductive material according to claim 6, characterized in that: In the step (3), the silicone oil stirring reaction temperature is 50-100° C., the reaction time is 3-6 hours, and the stirring rate is 400-600 r / min.

9. The method for preparing a novel polymer-based thermal conductive material according to claim 6, characterized in that: In the step (3), the mass ratio of silicone oil, self-made composite three-dimensional thermal conductive filler and metal-based catalyst is 50-100:20-40:1-5.